Laboratory investigation of antenna signals from dust impacts on spacecraft. Issue 7 (14th July 2015) - Collette, A.; Meyer, G.; Malaspina, D.; Sternovsky, Z.
Abstract We describe laboratory experiments which reproduce characteristic signals observed on spacecraft, believed to be caused by dust impact. A simulated spacecraft, including an antenna system using a facsimile of the preamplifier electronics from the STEREO/WAVES instrument, was bombarded by 10 km/s submicron‐sized dust at the University of Colorado Institute for Modeling Plasma, Atmospheres, and Cosmic Dust accelerator facility. Signal variation was investigated as a function of the DC potentials of both the spacecraft and the antennas. We observed (1) signals corresponding to modification of the spacecraft body potential, an important process believed to be responsible for the so‐called "triple hit" antenna signals on STEREO, (2) a few‐eV energy distribution for the electrons and ions released in the impact leading to (3) signals corresponding to direct recollection of a substantial fraction of the impact charge by the spacecraft antennas, even at modest antenna bias potentials. We also observe (4) an unexpected class of fast antenna signals, which do not appear to be caused by charge recollection by either the spacecraft or the antennas and may be induced by charge separation in the expanding plasma cloud. Similar signals are also commonly observed by the STEREO/WAVES instrument but have not previously been analyzed.